Dynamics of Constitutional Change in Indonesia: Challenges and Solutions in the Modern Era: Aspek Politik dan Hukum, Aspek Sosial dan Ekonomi, Peran Lembaga Negara dan Masyarakat dan Sejarah dan Proses Perubahan Konstitusi - Hudaifi, Muhammad (As-Shahifah : Journal of Constitutional Law and Governance, 2024)
The dynamics of constitutional change in Indonesia has becomean increasingly relevant issue in the modern era, amidst demandsfor reform, globalization and technological progress. The stateconstitution must be able to adapt to rapid socio-political changesin order to remain relevant to the needs of society. This researchaims to analyze the challenges and solutions in the process ofconstitutional change in Indonesia today. The method used in thisresearch is a normative approach with literature study, whichexamines various primary and secondary legal sources related toconstitutional amendments and changes in Indonesia. The findingsshow that the main challenges in changing the constitution inIndonesia include political tensions, resistance from conservativegroups, and amendment procedures that are quite complicated andrequire broad consensus. In addition, the rapid development ofinformation technology and continuously changing socialdynamics are often not reflected in existing constitutionalprovisions. The discussion in this research identifies severalsolutions, such as the need for more flexible reformulation ofamendment procedures, strengthening public participation in thechange process, and the application of technology to accelerate theadaptation of the constitution to changing times. In conclusion,although there are major challenges in changing the constitution inIndonesia, solutions based on openness, community participation,and the use of technology can be the key to achieving a moreresponsive and progressive constitution in the modern era.